Aplicación del programa basado en la teoría de las seis lecturas para mejorar la producción de textos argumentativos en los alumnos de segundo grado de educación secundaria - Seminario Chavez, Aida Rocío (2019)
ABSTRACT This study was carried out with the purpose of determining if the application of the Program based on the Theory of the six readings significantly improves the production of argumentative texts in second grade students of secondary education of the Educational Institution "Santo Domingo de Guzmán" of Chicama, in 2018. The research had 119 students as a study population; the sample consisted of 57 students; 28 in the experimental group and 29 in the control group; which have similar age and characteristics. The type of research is applied and with quasi-experimental design with two groups: experimental and control with pretest and posttest. After having applied the Program based on the Theory of the six readings, it significantly improves the production of argumentative texts, as evidenced by the "t" test; (te> tt; 17,06 > 1, 67), also manifested itself in the dimensions: cohesion and coherence reached the optimal level.